2005
DOI: 10.1007/s10048-005-0016-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of sporadic Creutzfeldt–Jakob disease with homozygous genotypes at PRNP codons 129 and 219 in the Korean population

Abstract: Human prion protein gene (PRNP) is considered an important gene in determining the incidence of human transmissible spongiform encephalopathies or prion diseases. Polymorphisms of PRNP at codon 129 in Europeans and codon 219 in Japanese may play an important role in the susceptibility to sporadic Creutzfeldt-Jakob disease (CJD); data regarding codon 129 in the Japanese population have led to divergent interpretations. In order to determine which, if any, of the PRNP genotypes in Korean people are associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 19 publications
2
67
0
Order By: Relevance
“…In our previous studies, we observed that polymorphisms in codons 129 and 219 of PRNP and a polymorphism at the 3′ untranslated region +28 of PRND are associated with the development of sporadic CJD in the Korean population [3,37,38]. However, CTSD C224T, PRNP 1368 polymorphism and polymorphisms in codons 56 and 174 of PRND did not affect the susceptibility to sporadic CJD [39,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, we observed that polymorphisms in codons 129 and 219 of PRNP and a polymorphism at the 3′ untranslated region +28 of PRND are associated with the development of sporadic CJD in the Korean population [3,37,38]. However, CTSD C224T, PRNP 1368 polymorphism and polymorphisms in codons 56 and 174 of PRND did not affect the susceptibility to sporadic CJD [39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Both codon 129 and 219 in PRNP were strongly associated with sporadic CJD [2,3,31]. Codon 129 of PRNP also has an effect on susceptibility in other types of human prion diseases [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms of PRNP at codons 129 and 219 have been shown to be a genetic factor for sporadic CJD [39]. We investigated whether the combined effects between PRNP polymorphisms and BKV subtypes are responsible for the susceptibility to sporadic CJD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, polymorphisms at codons 129 and/or 219 of PRNP are a key determinant of genetic susceptibility to sporadic Creutzfeldt-Jakob disease (CJD) [8][9][10] . Although the exact function of the prion protein is not fully known, current evidence suggests that it is involved in neuroprotection, oxidative stress and neurodevelopment.…”
Section: Introductionmentioning
confidence: 99%